Acrylonitrile catalyst as well as preparation method and application thereof

By introducing a bimodal mesoporous structure into the acrylonitrile catalyst, the problem of short contact time of the catalyst under high load is solved, high conversion and selectivity are improved, and the stable operation time of the catalyst is extended.

CN119236959AActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310776464.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-03
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing acrylonitrile catalyst has a short contact time between the catalyst and the raw material under high load operating conditions, resulting in poor catalyst activity and poor stability, making it difficult to maintain high conversion and selectivity under higher loads.

Method used

A acrylonitrile catalyst with a bimodal mesoporous structure is used to form mesoporous structures of different sizes and pore sizes by combining active metal components and support, thereby improving the specific surface area and reaction efficiency of the catalyst.

Benefits of technology

Maintaining high acrylonitrile single-way yield and conversion rate under higher reaction loads (such as 0.12h-1), extends the stable running time of the catalyst and improves the selectivity of the reaction product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236959A_ABST
    Figure CN119236959A_ABST
Patent Text Reader

Abstract

The invention provides an acrylonitrile catalyst as well as a preparation method and application thereof. The acrylonitrile catalyst comprises an active metal component and a carrier, the catalyst has a bimodal mesoporous structure, the pore volume of pores with the pore diameter of 2-12 nm accounts for 35%-55% of the total pore volume, and the most probable pore diameter is 5-8 nm; the pore volume of pores which are larger than 12 nm and smaller than or equal to 35 nm accounts for 45%-65% of the total pore volume, and the most probable pore diameter is 18-25 nm. The acrylonitrile catalyst provided by the invention can still have relatively high conversion rate and selectivity under a high-load operation condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a high-load catalyst for preparing acrylonitrile by propylene ammoxidation, and a preparation method and application thereof. Background Art

[0002] Acrylonitrile (AN) is a very important organic chemical raw material, which can be used for synthetic fiber acrylic fiber, and is also the raw material of acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN), nitrile rubber, adiponitrile, acrylamide and other derivatives. At present, the production of acrylonitrile by propylene ammoxidation is the mainstream technology for acrylonitrile production.

[0003] In actual applications, it is found that after long-term operation in a fluidized bed reactor, especially under high-load operation conditions, the contact time between the catalyst and the raw material is very short, and sufficient contact between the catalyst and the raw material cannot be achieved, resulting in limited catalyst activity and poor stability. Therefore, a key research direction for catalysts in this field is to develop a new catalyst for propylene ammoxidation to acrylonitrile that can operate stably under high loads.

[0004] CN1081488C introduces elements such as Na, Sr, and Mg to prepare a catalyst for preparing acrylonitrile by oxidizing propylene ammonia, which has the characteristics of being able to adapt to operation under high pressure and high load conditions and maintaining a high acrylonitrile yield, and can be used in industrial production. CN109772356A discloses a catalyst for preparing acrylonitrile by oxidizing propylene ammonia, which can simultaneously meet (1) the requirements of high catalyst load of industrial expansion equipment, and (2) reduce the production of carbonyl compounds acrolein and acrylic acid, and improve the operation cycle of the equipment; CN106955717A discloses a catalyst for preparing acrylonitrile by using inorganic non-metals such as activated clay, sodium montmorillonite or calcium montmorillonite and a silicon dioxide carrier for composite, roasting, and molding.

[0005] It can be seen that the current efforts to improve the operating load of acrylonitrile catalysts are mostly focused on changes in their components, such as increasing the types of metal elements, adjusting the carrier composition, etc. The load WWH of industrial acrylonitrile catalysts during reactions is usually 0.060 to 0.085 h -1 , that is, the unit mass of catalyst converts 0.06 to 0.085 unit mass of propylene per hour. Under this condition, the contact time between the catalyst and the raw material can usually reach 10 seconds. If the load is increased to a higher level, such as 0.12h -1 , the contact time will be further shortened to only about 5 seconds. However, how to make the catalyst still have a high conversion rate and selectivity under high load is a difficulty that needs to be solved urgently in this field. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides an acrylonitrile catalyst and a preparation method and application thereof. The acrylonitrile catalyst of the present invention can still have a high conversion rate and selectivity under high load operating conditions.

[0007] The first aspect of the present invention provides an acrylonitrile catalyst, comprising an active metal component and a carrier, wherein the catalyst has a bimodal mesoporous structure, wherein the pore volume occupied by pores with a pore diameter of 2 to 12 nm is 35% to 55% of the total pore volume, and the most probable pore diameter is 5 to 8 nm; the pore volume occupied by pores with a pore diameter of >12 nm and ≤35 nm is 45% to 65% of the total pore volume, and the most probable pore diameter is 18 to 25 nm.

[0008] Furthermore, the active metal component includes one or more of Mo, Bi, Fe, Ni, and Mg, preferably Mo, Bi, Fe, Ni, and Mg at the same time. The carrier includes silicon dioxide and / or a silicon-alumina mixed silicon-alumina-based carrier.

[0009] Furthermore, the catalyst has a small pore size of 5 to 8 nm originating from the dense packing of the active metal oxide itself, and a large pore size of 18 to 25 nm originating from the hard template of the polymer resin.

[0010] Furthermore, the polymer resin includes at least one of phenolic resin, urea-formaldehyde resin or melamine resin, and preferably urea-formaldehyde resin.

[0011] Furthermore, based on the weight of the catalyst, the total content of active metal components in terms of oxides is 45% to 60%, and the content of the carrier is 40% to 55%.

[0012] Furthermore, the catalyst has a specific surface area of ​​45 to 80 m 2 / g.

[0013] The second aspect of the present invention provides a method for preparing an acrylonitrile catalyst, comprising: dissolving and mixing an active component and a carrier, further compounding with a polymer resin to obtain a mixed slurry, and obtaining the mixed slurry by drying and calcining.

[0014] Furthermore, the preparation method of the acrylonitrile catalyst specifically comprises:

[0015] (1) heating and dissolving a precursor of an active component containing Mo, and mixing it with a carrier;

[0016] (2) mixing a precursor solution containing at least one active metal component of Bi, Fe, Ni, and Mg with the material obtained in step (1) to obtain a mixed slurry;

[0017] (3) The polymer monomer is heated and dissolved in water, and the mixture is added to the mixed slurry of step (2), followed by the addition of formaldehyde monomer solution and alkaline solution, and the mixture is mixed and stirred to obtain a final slurry, which is then dried and calcined to obtain an acrylonitrile catalyst.

[0018] Furthermore, the precursor containing active metal elements is a water-soluble salt containing active metal elements, wherein the active component precursor containing Mo is preferably an oxygen-containing acid ammonium salt containing Mo, preferably (NH4)6Mo7O 24 The precursor solution containing at least one active metal component of Bi, Fe, Ni, Mg is one or more of halides, alkoxides, nitrates or acetates, preferably nitrates, such as bismuth nitrate, iron nitrate, nickel nitrate, magnesium nitrate, etc.

[0019] Furthermore, in the present invention, the heating and dissolving can be carried out at a conventional temperature in the art to achieve sufficient dissolution and mixing.

[0020] Furthermore, in step (1), the carrier is selected from silica sol, solid phase silica or silica / alumina molecular sieve carrier, preferably silica sol.

[0021] Furthermore, in step (3), the polymer monomer is selected from at least one of urea, phenol, resorcinol and melamine, preferably urea and / or phenol, and more preferably urea.

[0022] Furthermore, in step (3), the total amount of the formaldehyde monomer and the polymer monomer added is 5% to 20% of the total mass of the active metal precursor, preferably 8% to 15%.

[0023] Furthermore, in step (3), the mass concentration of the formaldehyde monomer solution is 20% to 50%, preferably 25% to 40%. The molar ratio of the amount of the added formaldehyde monomer to the polymer monomer is preferably 0.8:1 to 1.5:1.

[0024] Furthermore, in step (3), the alkaline solution is selected from at least one of an aqueous ammonia solution, a sodium hydroxide solution and a potassium hydroxide solution, preferably an aqueous ammonia solution. The mass concentration of the alkaline solution is preferably 10% to 15%, and the mass ratio of the amount of the alkaline solution added to the formaldehyde monomer solution is preferably 0.1:1 to 0.5:1.

[0025] Furthermore, in step (3), the stirring conditions include: time 15 to 30 min, temperature 80 to 120° C., and stirring speed 150 to 350 rpm.

[0026] Furthermore, in step (3), the drying conditions include: a drying temperature of 200 to 480°C, preferably 300 to 400°C, a drying time of 0.5 to 4 hours, preferably 0.5 to 1.5 hours. The drying method is spray drying, the heat source is air, and the average diameter of the spray droplets is 40 to 200 μm, preferably 40 to 180 μm.

[0027] Furthermore, in step (3), the calcination conditions include: a calcination temperature of 200 to 700° C., preferably 400 to 650° C., and a calcination time of 3 to 8 hours, preferably 4 to 6 hours. The calcination is carried out in an oxygen-containing atmosphere, such as air atmosphere.

[0028] A third aspect of the present invention provides use of the acrylonitrile catalyst or the acrylonitrile catalyst prepared by the method in preparing acrylonitrile.

[0029] The application is specifically as follows: in the presence of the acrylonitrile catalyst, propylene undergoes an ammoxidation reaction in the presence of ammonia and oxygen to generate acrylonitrile.

[0030] The specific reaction conditions include: the molar ratio of propylene / ammonia / air (based on the oxygen contained) is 1:1.2-1.3:9.6-10.0, the reaction temperature is 420-435°C, the reaction pressure (gauge pressure) is 0.06-0.14 MPa, and the reaction catalyst load is 0.08-0.12 h -1 , preferably 0.09~0.12h -1 .

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] The acrylonitrile catalyst of the present invention has a specific bimodal mesoporous structure. The inventors have found that the specific pore distribution of the present invention, wherein small-sized mesopores of 5 to 8 nm are conducive to the improvement of the specific surface area of ​​the catalyst and promote the full contact and reaction between the raw material and the catalyst, and large-sized mesopores of 18 to 25 nm are conducive to the timely desorption of the product from the catalyst surface, reducing deep oxidation and improving the selectivity of the reaction product acrylonitrile, thereby ensuring the stable progress of the reaction under a higher reaction load, that is, a shorter contact time.

[0033] In the method for preparing the acrylonitrile catalyst of the present invention, two mesopores of different sizes are formed by polymer-induced assembly and metal oxides' own dense packing. Compared with other pore-forming agents, the mesopore distribution of the catalyst of the present invention is more concentrated and does not affect the overall catalytic performance of the catalyst. The obtained acrylonitrile catalyst can react with the catalyst under a higher reaction load (e.g., 0.12h -1 ) Maintain a high acrylonitrile per-pass yield for a long time. After long-term operation, it can still maintain a high propylene conversion rate and acrylonitrile per-pass yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the pore size distribution diagram of the acrylonitrile catalyst prepared in Example 1;

[0035] Figure 2 This is the pore size distribution diagram of the acrylonitrile catalyst prepared in Comparative Example 1;

[0036] Figure 3 This is the pore size distribution diagram of the acrylonitrile catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION

[0037] In order to explain the present invention more clearly, the present invention is further described below in conjunction with embodiments and drawings. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0038] The method for measuring the specific surface area and pore size in the present invention adopts a Tristar physical adsorption instrument for measurement. Before the sample is tested, it is necessary to perform a heating vacuum degassing treatment. The porosity of the sample is measured at 77K, and the specific surface area is calculated by the Brunauer-Emmett-Teller (BET) method. The distribution of pore size and pore volume can be calculated from the isothermal adsorption branch using the Barrettner-Joyner-Halenda (BJH) model.

[0039] In the present invention, gas chromatography is used to perform online analysis on the product gas, and the conversion rate of propylene, the selectivity of acrylonitrile and the single-pass yield are used as indicators for evaluating the performance of the catalyst, and the definitions of the two are as follows:

[0040] Acrylonitrile conversion (%) = (moles of propylene reacted / moles of propylene fed) × 100%

[0041] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene reacted) × 100%

[0042] Acrylonitrile single-pass yield (%) = (acrylonitrile produced moles / propylene feed moles) × 100%

[0043] [Example 1]

[0044] (1) 93.7 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0045] (2) 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0046] (3) Weigh 14.0 g of urea, dissolve it in water and add it to the mixed slurry II, then add 25.0 g of formaldehyde solution with a mass concentration of 28% and 5.0 g of ammonia solution with a mass concentration of 14%, stir at 100° C. and 300 rpm for 0.5 hour to obtain slurry. Spray dry the slurry at a drying temperature of 350° C. for 0.5 hour to obtain granules, and calcine the granules at 600° C. in air for 3 hours to obtain acrylonitrile catalyst A, whose general component formula is:

[0047] 50%Mo 12.00 Bi 0.43 Fe 1.63 Ni 3.72 Mg 1.38 O 44.18 +50%SiO2

[0048] The specific surface area of ​​acrylonitrile catalyst A is 69.3 m 2 / g, with a bimodal mesoporous structure, see Figure 1 Among them, pores with a pore size of 2 to 12 nm account for 45% of the total pore volume, and the most probable pore size is 6.0 nm; pores with a pore size of >12 nm and ≤35 nm account for 54% of the total pore volume, and the most probable pore size is 21 nm.

[0049] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.26%, the acrylonitrile selectivity was 83.81%, and the acrylonitrile single-pass yield was 82.35%. After 500 hours of operation, the propylene conversion rate was 97.95%, the acrylonitrile selectivity was 83.57%, and the acrylonitrile single-pass yield was 81.86%.

[0050] [Example 2]

[0051] (1) 93.7 g (NH4)6Mo7O 244H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0052] (2) 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0053] (3) Weigh 22.0 g of resorcinol, dissolve it in water and add it to the mixed slurry II, then add 25.0 g of a 28% formaldehyde solution and 5.0 g of a 14% ammonia solution in sequence, stir at 100° C. and 300 rpm for 0.5 hour to obtain a slurry. Spray dry the slurry at 350° C. for 0.5 hour to obtain a granular material, and calcine the granular material at 600° C. in air for 3 hours to obtain an acrylonitrile catalyst B.

[0054] The specific surface area of ​​acrylonitrile catalyst B is 68.4 m 2 / g, with a bimodal mesoporous structure, in which pores with a pore diameter of 2-12nm account for 44% of the total pore volume, and the most probable pore diameter is 6.5nm; pores with a pore diameter of >12nm and ≤35nm account for 55% of the total pore volume, and the most probable pore diameter is 22.3nm.

[0055] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.19%, the acrylonitrile selectivity was 83.76%, and the acrylonitrile single-pass yield was 82.24%. After 500 hours of operation, the propylene conversion rate was 97.78%, the acrylonitrile selectivity was 83.50%, and the acrylonitrile single-pass yield was 81.65%.

[0056] [Example 3]

[0057] (1) 103.1 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 105 g of 600-mesh ZSM-5 molecular sieve was added and stirred to obtain material I;

[0058] (2) 10.6 g Bi(NO3)3·5H2O, 54.7 g Ni(NO3)2·6H2O, 33.2 g Fe(NO3)3·9H2O, and 17.6 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0059] (3) 15.4 g of urea was weighed, dissolved in water, and added to the mixed slurry II, and then 25.0 g of a 28% formaldehyde solution and 7.0 g of a 10% ammonia solution were added thereto in sequence, and stirred at 100° C. and 300 rpm for 0.5 hour to obtain a slurry. The slurry was spray-dried at a drying temperature of 350° C. for 0.5 hour to obtain a granular material, which was calcined at 600° C. in an air atmosphere for 3 hours to obtain an acrylonitrile catalyst C.

[0060] The specific surface area of ​​acrylonitrile catalyst C is 72.3 m 2 / g, with a bimodal mesoporous structure, in which pores with a pore size of 2-12nm account for 48% of the total pore volume, and the most probable pore size is 7.1nm; pores with a pore size of >12nm and ≤35nm account for 50% of the total pore volume, and the most probable pore size is 24.0nm.

[0061] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.10%, the acrylonitrile selectivity was 83.68%, and the acrylonitrile single-pass yield was 82.09%. After 500 hours of operation, the propylene conversion rate was 97.68%, the acrylonitrile selectivity was 83.37%, and the acrylonitrile single-pass yield was 81.44%.

[0062] [Example 4]

[0063] (1) 93.7 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0064] (2) 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0065] (3) 14.0 g of urea was weighed, dissolved in water, and added to the mixed slurry II, and then 25.0 g of a 28% formaldehyde solution and 14.0 g of a 5% sodium hydroxide aqueous solution were added thereto in sequence, and stirred at 120° C. and 250 rpm for 0.5 hour to obtain a slurry. The slurry was spray-dried at a drying temperature of 350° C. for 0.5 hour to obtain a granular material, which was calcined at 620° C. in an air atmosphere for 3 hours to obtain an acrylonitrile catalyst D.

[0066] The specific surface area of ​​acrylonitrile catalyst D is 65.8 m 2 / g, with a bimodal mesoporous structure, in which pores with a pore size of 2-12nm account for 50% of the total pore volume, and the most probable pore size is 7.2nm; pores with a pore size of >12nm and ≤35nm account for 49% of the total pore volume, and the most probable pore size is 23.5nm.

[0067] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.18%, the acrylonitrile selectivity was 83.78%, and the acrylonitrile single-pass yield was 82.26%. After 500 hours of operation, the propylene conversion rate was 97.76%, the acrylonitrile selectivity was 83.48%, and the acrylonitrile single-pass yield was 81.61%.

[0068] [Example 5]

[0069] (1) 93.7 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0070] (2) 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0071] (3) Weigh 25.2 g of urea, dissolve it in water and add it to the mixed slurry II, then add 45 g of a formaldehyde solution with a mass concentration of 28% and 9.0 g of an ammonia solution with a mass concentration of 14% in sequence, stir at 100° C. and 300 rpm for 0.5 hour to obtain a slurry. The slurry is spray-dried at a drying temperature of 350° C. for 0.5 hour to obtain a granular material, which is calcined at 600° C. in an air atmosphere for 3 hours to obtain an acrylonitrile catalyst E.

[0072] The specific surface area of ​​acrylonitrile catalyst E is 60.5 m 2 / g, with a bimodal mesoporous structure, in which pores with a pore size of 2-12nm account for 47% of the total pore volume, and the most probable pore size is 7.9nm; pores with a pore size of >12nm and ≤35nm account for 51% of the total pore volume, and the most probable pore size is 24.5nm.

[0073] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.08%, the acrylonitrile selectivity was 83.65%, and the acrylonitrile single-pass yield was 82.04%. After 500 hours of operation, the propylene conversion rate was 97.67%, the acrylonitrile selectivity was 83.25%, and the acrylonitrile single-pass yield was 81.31%.

[0074] [Comparative Example 1]

[0075] (1) 93.7 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0076] (2) 9.6 g of Bi(NO3)3·5H2O, 49.7 g of Ni(NO3)2·6H2O, 30.2 g of Fe(NO3)3·9H2O, and 16.2 g of Mg(NO3)2·6H2O were dissolved in water, added to material I, and stirred at 100°C and 300 rpm for 0.5 hour to obtain a mixed slurry II. The slurry was spray-dried at a drying temperature of 350°C for 0.5 hour to obtain a granular material, which was calcined at 600°C in an air atmosphere for 3 hours to obtain an acrylonitrile catalyst F.

[0077] The specific surface area of ​​acrylonitrile catalyst F is 37.0 m 2 / g, does not have a bimodal mesoporous structure, and the most probable pore diameter is 9.1nm. Figure 2 .

[0078] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 95.24%, the acrylonitrile selectivity was 81.27%, and the acrylonitrile single-pass yield was 77.40%. After 500 hours of operation, the propylene conversion rate was 93.06%, the acrylonitrile selectivity was 78.05%, and the acrylonitrile single-pass yield was 72.63%.

[0079] [Comparative Example 2]

[0080] (1) 93.7 g (NH4)6Mo7O 24 4H2O was heated and dissolved in water, and 350 g of 30% silica sol was added to obtain material I;

[0081] (2) 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O were dissolved in water and added to material I to obtain a mixed slurry II;

[0082] (3) Weigh 35.0 g of urea, dissolve it in water and add it to the mixed slurry II, then add 62.5 g of formaldehyde solution with a mass concentration of 28% and 12.5 g of ammonia solution with a mass concentration of 14% in sequence, stir at 100° C. and 300 rpm for 0.5 hour to obtain slurry. Spray dry the slurry at a drying temperature of 350° C. for 0.5 hour to obtain granules, and calcine the granules at 600° C. in air for 3 hours to obtain acrylonitrile catalyst G.

[0083] The specific surface area of ​​acrylonitrile catalyst G is 42.6 m 2 / g, with a bimodal mesoporous structure, but the most probable pore diameters are located at 13.1nm and 35.4nm, see Figure 3 .

[0084] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.12h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 93.65%, the acrylonitrile selectivity was 79.86%, and the acrylonitrile single-pass yield was 74.79%. After 500 hours of operation, the propylene conversion rate was 91.14%, the acrylonitrile selectivity was 75.9%, and the acrylonitrile single-pass yield was 69.18%.

[0085] Table 1 Comparison of parameters of catalysts in the examples and comparative examples

[0086]

[0087] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An acrylonitrile catalyst comprising an active metal component and a carrier, characterized in that: The catalyst has a bimodal mesoporous structure, wherein pores with a pore diameter of 2 to 12 nm account for 35% to 55% of the total pore volume, and the most probable pore diameter is 5 to 8 nm; pores with a pore diameter of more than 12 nm and less than or equal to 35 nm account for 45% to 65% of the total pore volume, and the most probable pore diameter is 18 to 25 nm.

2. The catalyst according to claim 1, characterized in that The active metal component includes one or more of Mo, Bi, Fe, Ni, and Mg, preferably includes Mo, Bi, Fe, Ni, and Mg at the same time; the carrier includes silica and / or a silica / alumina mixed silica-alumina based carrier.

3. The catalyst according to claim 1, characterized in that Based on the weight of the catalyst, the total content of active metal components in the form of oxides is 45-60%, and the content of the carrier is 40-55%.

4. The method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: include: After the active component and the carrier are dissolved and mixed, they are further compounded with a polymer resin to obtain a mixed slurry, which is then obtained by drying and calcining.

5. The method according to claim 4, characterized in that The polymer resin includes at least one of phenolic resin, urea-formaldehyde resin or melamine resin, and is preferably urea-formaldehyde resin.

6. The method according to claim 4, characterized in that The preparation method of the acrylonitrile catalyst specifically comprises: (1) heating and dissolving a precursor of an active component containing Mo, and mixing it with a carrier; (2) mixing a precursor solution containing at least one active metal component of Bi, Fe, Ni, and Mg with the material obtained in step (1) to obtain a mixed slurry; (3) The polymer monomer is heated and dissolved in water, and the mixture is added to the mixed slurry of step (2), followed by the addition of formaldehyde monomer solution and alkaline solution, and the mixture is mixed and stirred to obtain a final slurry, which is then dried and calcined to obtain an acrylonitrile catalyst.

7. The method according to claim 6, characterized in that In step (3), the polymer monomer is selected from at least one of urea, phenol, resorcinol and melamine, preferably urea and / or phenol, more preferably urea; and / or, In step (3), the total amount of the formaldehyde monomer and the polymer monomer added is 5% to 20% of the total mass of the active metal precursor, preferably 8% to 15%.

8. The method according to claim 6, characterized in that In step (3), the mass concentration of the formaldehyde monomer solution is 20% to 50%, preferably 25% to 40%; the molar ratio of the amount of the added formaldehyde monomer to the polymer monomer is preferably 0.8:1 to 1.5:

1.

9. The method according to claim 6, characterized in that In step (3), the alkaline solution is selected from at least one of an aqueous ammonia solution, a sodium hydroxide solution and a potassium hydroxide solution; the mass concentration of the alkaline solution is preferably 10% to 15%; the mass ratio of the amount of the alkaline solution added to the formaldehyde monomer solution is preferably 0.1:1 to 0.5:

1.

10. The method according to claim 6, characterized in that In step (3), the drying conditions include: a drying temperature of 200 to 480° C., preferably 300 to 400° C., and a drying time of 0.5 to 4 hours, preferably 0.5 to 1.5 hours; and / or the roasting conditions include: a roasting temperature of 200 to 700° C., preferably 400 to 650° C., and a roasting time of 3 to 8 hours, preferably 4 to 6 hours.

11. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the method according to any one of claims 4 to 10 in the preparation of acrylonitrile.

Citation Information

Patent Citations

  • Acrylonitrile catalyst

    CN107398288A

  • Catalyst for propane dehydrogenation and preparation method thereof, and method for preparing propylene from propane through dehydrogenation

    CN109384639A

  • Propane dehydrogenation catalyst and preparation method thereof and method for preparing propylene by propane dehydrogenation

    CN109745978A

  • Ammoxidation catalyst for fluidized-beds and manufacturing method of acrylonitrile or methacrylonitrile using it

    JP2009285581A

  • HCMS carbon capsule, electrocatalysts for fuel cell supported by HCMS carbon capsule, and method of preparing the same

    US20050032635A1